A composite photothermal material and its preparation method and application

Through the Ag-loaded MXene and chitosan composite, the problems of insufficient environmental pressure and photothermal efficiency of traditional water purification methods are solved, and efficient solar water evaporation and antibacterial performance are achieved, which significantly improves the water purification effect.

CN116178800BActive Publication Date: 2024-12-27SHANDONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310102086.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-09
Publication Date
2024-12-27
Estimated Expiration
2043-02-09

AI Technical Summary

Technical Problem

Traditional water purification methods are under great environmental pressure and by-products are harmful to health. The light capture ability and photothermal conversion efficiency of pure hydrogel materials are insufficient, limiting their antibacterial and solar water evaporation efficiency.

Method used

Ag-loaded two-dimensional MXene nanosheets and three-dimensional chitosan hydrogel network composite material were used to prepare high-concentration MXene suspension by etching method, and then oxidized silver ions and reducing agent were added to cross-linked with chitosan to form composite photothermal Materials used in the fields of antibacterial and solar water evaporation.

Benefits of technology

It has achieved efficient solar energy utilization efficiency and water purification performance, excellent antibacterial performance, evaporation efficiency reaches 94.9%, the purified water meets the drinking water standards of the World Health Organization, and significantly reduces the concentration of pollutants in sewage and seawater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116178800B_ABST
    Figure CN116178800B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of functional materials, and specifically relates to a composite photothermal material and its preparation method and application. The composite photothermal material is prepared by Ag-loaded two-dimensional MXene nanosheets and three-dimensional chitosan hydrogel network. It can kill 100% of Escherichia coli and 100% of Staphylococcus aureus after 30 minutes of illumination, achieving a 3.22kg m ‑2 h ‑1 It has high evaporation efficiency and also has excellent performance in seawater desalination and sewage purification, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional materials, and specifically relates to a composite photothermal material and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] With the growth of the world's population and the development of global industrialization, environmental pollution has become a global problem that needs to be solved urgently, threatening human life, health and safety. Among them, the shortage of clean water resources seriously restricts the development of countries around the world, mainly developing countries. In addition, due to the abuse of antibiotics, the emergence of drug-resistant bacteria in water resources has also made safe water use more difficult. However, traditional water purification methods including chemical precipitation, ozone and ultraviolet radiation, membrane filtration, etc. have caused tremendous environmental pressure, and the byproducts produced during the disinfection process are also detrimental to human health. Therefore, it is necessary to develop new and efficient clean water production technologies to reduce environmental pressure, reduce costs, and ensure the demand for safe water for human use.

[0004] Photothermal technology driven by solar energy can achieve sewage and seawater purification through the interfacial water evaporation process and is considered to be one of the most promising technologies. Compared with traditional passive desalination, it exhibits the characteristics of high heat utilization and evaporation efficiency, flexible carrying, low cost, and feasible installation. In recent years' research, photothermal water gel materials have shown great advantages. Although hydrogels have rich network structures that give them excellent water transport performance, the light capture ability and photothermal conversion efficiency of pure hydrogel materials still have certain defects, which to some extent restrict their antibacterial ability and solar water evaporation efficiency. Therefore, the preparation of efficient solar antibacterial water evaporation materials through the screening of hydrogel components is of great significance for water purification technology. Summary of the invention

[0005] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a composite photothermal material and its preparation method and application. The composite photothermal material is prepared by Ag-loaded two-dimensional MXene nanosheets and three-dimensional chitosan hydrogel network, which can be applied to the antibacterial field and solar water evaporation field, and can achieve high solar energy utilization efficiency and water purification performance under mild conditions.

[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a composite photothermal material, comprising the following steps:

[0008] The MAX phase Ti3AlC2 powder was etched to remove Al and then washed repeatedly with deionized water to obtain Ti3C2T x , Ti3C2T x Re-dispersed in water, centrifuged after sonication, and obtained a high-concentration MXene suspension;

[0009] The MXene suspension is added with an oxidizing silver ion solution under vigorous stirring, and after uniform mixing, an excess reducing agent is added and further stirred to obtain an Ag / MXene composite material, which is washed with deionized water and then freeze-dried;

[0010] The Ag / MXene composite material is added to the chitosan solution under stirring, and then an excess amount of a cross-linking agent is added to the suspension, and the suspension is allowed to stand until an Ag / MXene / chitosan composite photothermal material is formed.

[0011] In a second aspect, the present invention provides a composite photothermal material obtained by the preparation method of the composite photothermal material described in the first aspect.

[0012] In a third aspect, the present invention provides application of the composite photothermal material described in the second aspect in the antibacterial field.

[0013] In a fourth aspect, the present invention provides application of the composite photothermal material described in the second aspect in the field of water evaporation purification.

[0014] The beneficial effects achieved by one or more technical solutions of the present invention are as follows:

[0015] (1) The present invention provides a novel method for preparing a composite photothermal material, which is simple, highly practical, easy to promote, and has good application prospects.

[0016] (2) The present invention provides a novel composite photothermal material. In the porous structure, Ag / MXene nanosheets serve as the photothermal center of the solar steam generator, while the chitosan hydrogel platform has abundant water-rich pores at the micrometer scale, ensuring that water is continuously transported to the evaporation point. The material has excellent light capture, photothermal conversion and water transport performance. Its application in the field of water evaporation effectively solves the high cost and high requirements of energy-intensive water purification technology, and the solar energy conversion efficiency reaches 94.9%.

[0017] (3) The composite photothermal material prepared by the present invention has excellent antibacterial properties and has excellent light-induced antibacterial properties against Staphylococcus aureus and Escherichia coli. 100% of Escherichia coli and 100% of Staphylococcus aureus can be killed by irradiation for 30 minutes.

[0018] (4) The composite photothermal material prepared by the present invention can be further prepared into an evaporator, which imitates the tree roots in nature and maintains a continuous water transport channel, achieving a water transport capacity of 3.22 kg m under sunlight. -2 h -1 It has high evaporation efficiency and also has excellent performance in seawater desalination and sewage purification. The purified liquid water meets the drinking water quality standards of the World Health Organization. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0020] Figure 1 The Ag prepared in Example 1 0.2 MXene 0.8 Scanning electron microscope (SEM) images and Ag 0.2 MXene 0.8 X-ray energy spectrum element mapping (EDS) images of Ag and MXene in the composite material;

[0021] Figure 2 This is a SEM image of the freeze-dried composite photothermal material prepared in Example 1;

[0022] Figure 3 X-ray diffraction (XRD) patterns of the composite photothermal material, chitosan hydrogel and chitosan powder prepared in Example 1 and Comparative Example 1, wherein a is chitosan powder, b is Ch hydrogel, and c is AM / Ch hydrogel;

[0023] Figure 4 The antibacterial performance test diagram of the composite photothermal material prepared in Example 1, wherein a is a photo of Escherichia coli colonies under different illumination times in different culture media, and b is a photo of Staphylococcus aureus colonies under different illumination times in different culture media; c is a photo of anti-Escherichia coli activity under different illumination times in different culture media, and d is a photo of anti-Staphylococcus aureus activity under different illumination times in different culture media;

[0024] Figure 5 This is an evaporation performance diagram of the composite photothermal material evaporator prepared in Example 6, wherein a is an evaporator preparation flow chart, b is a mass change chart, c is an evaporation rate chart, and d is a temperature change chart;

[0025] Figure 6 This is a comparison chart of the composite photothermal material evaporator prepared in Example 6 before and after seawater desalination and sewage purification, a is a comparison chart before and after different ion concentrations, and b is a comparison chart before and after methyl orange and methyl blue removal. DETAILED DESCRIPTION

[0026] A first typical embodiment of the present invention is a method for preparing a composite photothermal material, comprising the following steps:

[0027] The MAX phase Ti3AlC2 powder was etched to remove Al and then washed repeatedly with deionized water to obtain Ti3C2T x , Ti3C2T x Re-dispersed in water, centrifuged after sonication, and obtained a high-concentration MXene suspension;

[0028] The MXene suspension is added with an oxidizing silver ion solution under vigorous stirring, and after uniform mixing, an excess reducing agent is added and further stirred to obtain an Ag / MXene composite material, which is washed with deionized water and then freeze-dried;

[0029] The Ag / MXene composite material is added to the chitosan solution under stirring, and then an excess amount of a cross-linking agent is added to the suspension, and the suspension is allowed to stand until an Ag / MXene / chitosan composite photothermal material is formed.

[0030] In one or more examples of this implementation, the etching method specifically comprises slowly adding LiF into hydrochloric acid to form an etching solution, then slowly adding Ti3AlC2 powder into the above solution and stirring, and keeping the solution at 35°C for 24-48h.

[0031] In one or more examples of this implementation, deionized water is repeatedly washed until the pH is > 6; and the ultrasonic time is 20-60 min.

[0032] In one or more examples of this implementation, the oxidizing silver ion solution is a silver nitrate solution, the reducing agent is a sodium borohydride aqueous solution or a potassium borohydride aqueous solution, and the stirring time is 20-60 min.

[0033] In one or more examples of this embodiment, the mass ratio of silver to MXene in the oxidizing silver ion solution is 1-2:9-8. When the ratio of Ag nanoparticles relative to the total mass of Ag and MXene is higher than 20wt%, the two-dimensional morphology of MXene will be destroyed due to the oxidation of silver nitrate.

[0034] In one or more examples of this embodiment, the chitosan solution is an acetic acid solution of chitosan, and the concentration of the acetic acid is 0.4-0.5 mol / L; the cross-linking agent is a hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 5-7 mol / L.

[0035] In one or more examples of this embodiment, the mass ratio of the Ag / MXene composite material to chitosan is 0.25-0.35:1.

[0036] The second typical embodiment of the present invention is a composite photothermal material, which is obtained by the preparation method of the composite photothermal material described in the first typical embodiment. The composite photothermal material includes a two-dimensional structural material MXene nanosheet, uniformly dispersed Ag nanoparticles and a three-dimensional natural antibacterial polymer material chitosan, and has a rich water-rich pore network structure. MXene nanosheets have excellent antibacterial and photothermal properties, and can synergistically enhance the antibacterial properties with Ag nanoparticles.

[0037] In one or more examples of this embodiment, the Ag is Ag nanoparticles, the size of Ag is 2-15 nm, the MXene is a two-dimensional nanosheet, the Ag nanoparticles are uniformly dispersed on the MXene, and the chitosan is a three-dimensional structure.

[0038] The third typical embodiment of the present invention is the application of the composite photothermal material described in the second typical embodiment in the antibacterial field.

[0039] A fourth typical embodiment of the present invention is the application of the composite photothermal material described in the second typical embodiment in the field of water evaporation purification.

[0040] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0041] Example 1

[0042] 2g LiF was slowly added to a polytetrafluoroethylene beaker containing 30ml hydrochloric acid (12mol / L) and stirred at 35°C for 30 minutes to obtain an etching solution. 2g Ti3AlC2 powder was slowly added to the above solution and kept at 35°C for 24 hours. After the etching process, the obtained product was repeatedly washed with deionized water and centrifuged at 3500rpm several times until the pH value was greater than 6. The obtained Ti3C2T x The clay was redispersed in deionized water, sonicated for 30 min, and hand-shaken to obtain a highly concentrated MXene suspension.

[0043] The above MXene suspension was added with an appropriate amount of AgNO3 solution under vigorous stirring to make the mass ratio of Ag:MXene = 2:8, and then an excess of sodium borohydride aqueous solution (1 mol / L) was quickly injected into the suspension under stirring, and the resulting suspension was further stirred for 30 minutes to produce an Ag / MXene composite material (denoted as Ag 0.2 MXene 0.8 ), washed several times with deionized water by centrifugation, and then freeze-dried.

[0044] 0.1 g of chitosan powder was added to 2.5 mL of acetic acid solution (0.42 mol / L) under stirring to produce a chitosan solution, and then 30 mg of Ag was added under stirring. 0.2 MXene 0.8 The powder was introduced into the chitosan solution. Subsequently, an excess of hydrochloric acid solution (6 mol / L) was slowly added to the mixed suspension, and the mixture was kept still until the Ag / MXene / chitosan composite photothermal material was formed, which was recorded as AM / Ch hydrogel.

[0045] like Figure 1 As shown, Ag 0.2 MXene 0.8 The MXene in the nanosheets maintains a layered structure, and the Ag nanoparticles are evenly distributed on the surface of the MXene nanosheets. Figure 2 As shown, the AM / Ch hydrogel has a porous network structure, which is beneficial for water transport during solar steam generation.

[0046] Example 2

[0047] 2g LiF was slowly added to a polytetrafluoroethylene beaker containing 30ml hydrochloric acid (12mol / L) and stirred at 35°C for 30 minutes to obtain an etching solution. 2g Ti3AlC2 powder was slowly added to the above solution and kept at 35°C for 24 hours. After the etching process, the obtained product was repeatedly washed with deionized water and centrifuged at 3500rpm several times until the pH value was greater than 6. The obtained Ti3C2T x The clay was redispersed in deionized water, sonicated for 30 min, and hand-shaken to obtain a highly concentrated MXene suspension.

[0048] The above MXene suspension was added with an appropriate amount of AgNO3 solution under vigorous stirring to make the mass ratio of Ag:MXene = 1:9, and then an excess of sodium borohydride aqueous solution (1 mol / L) was quickly injected into the suspension under stirring, and the resulting suspension was further stirred for 30 minutes to produce an Ag / MXene composite material (denoted as Ag 0.1 MXene 0.9 ), washed several times with deionized water by centrifugation, and then freeze-dried.

[0049] 0.1 g of chitosan powder was added to 2.5 mL of acetic acid solution (0.42 mol / L) under stirring to produce a chitosan solution, and then 30 mg of Ag was added under stirring. 0.1 MXene 0.9 The powder was introduced into the chitosan solution. Subsequently, an excess of hydrochloric acid solution (6 mol / L) was slowly added to the mixed suspension, and the mixture was kept still until the Ag / MXene / chitosan composite photothermal material was formed.

[0050] Example 3

[0051] 2g LiF was slowly added to a polytetrafluoroethylene beaker containing 30ml hydrochloric acid (12mol / L) and stirred at 35°C for 30 minutes to obtain an etching solution. 2g Ti3AlC2 powder was slowly added to the above solution and kept at 35°C for 24 hours. After the etching process, the obtained product was repeatedly washed with deionized water and centrifuged at 3500rpm several times until the pH value was greater than 6. The obtained Ti3C2T x The clay was redispersed in deionized water, sonicated for 30 min, and hand-shaken to obtain a highly concentrated MXene suspension.

[0052] The above MXene suspension was added with an appropriate amount of AgNO3 solution under vigorous stirring to make the mass ratio of Ag:MXene = 2:8, and then an excess of sodium borohydride aqueous solution (1 mol / L) was quickly injected into the suspension under stirring, and the resulting suspension was further stirred for 30 minutes to produce an Ag / MXene composite material (denoted as Ag 0.2 MXene 0.8 ), washed several times with deionized water by centrifugation, and then freeze-dried.

[0053] 0.1 g of chitosan powder was added to 2.5 mL of acetic acid solution (0.42 mol / L) under stirring to produce a chitosan solution, and then 25 mg of Ag was added under stirring. 0.2 MXene 0.8 The powder was introduced into the chitosan solution. Subsequently, an excess of hydrochloric acid solution (6 mol / L) was slowly added to the mixed suspension, and the mixture was kept still until the Ag / MXene / chitosan composite photothermal material was formed.

[0054] Example 4

[0055] 2g LiF was slowly added to a polytetrafluoroethylene beaker containing 30ml hydrochloric acid (12mol / L) and stirred at 35°C for 30 minutes to obtain an etching solution. 2g Ti3AlC2 powder was slowly added to the above solution and kept at 35°C for 24 hours. After the etching process, the obtained product was repeatedly washed with deionized water and centrifuged at 3500rpm several times until the pH value was greater than 6. The obtained Ti3C2T x The clay was redispersed in deionized water, sonicated for 30 min, and hand-shaken to obtain a highly concentrated MXene suspension.

[0056] The above MXene suspension was added with an appropriate amount of AgNO3 solution under vigorous stirring to make the mass ratio of Ag:MXene = 2:8, and then an excess of sodium borohydride aqueous solution (1 mol / L) was quickly injected into the suspension under stirring, and the resulting suspension was further stirred for 30 minutes to produce an Ag / MXene composite material (denoted as Ag 0.2 MXene 0.8 ), washed several times with deionized water by centrifugation, and then freeze-dried.

[0057] 0.1 g of chitosan powder was added to 2.5 mL of acetic acid solution (0.42 mol / L) under stirring to produce a chitosan solution, and then 35 mg of Ag was added under stirring. 0.2 MXene 0.8 The powder was introduced into the chitosan solution. Subsequently, an excess of hydrochloric acid solution (6 mol / L) was slowly added to the mixed suspension, and the mixture was kept still until the Ag / MXene / chitosan composite photothermal material was formed.

[0058] Comparative Example 1

[0059] 0.1 g of chitosan powder was added to 2.5 mL of acetic acid solution (0.42 mol / L) under stirring to produce a chitosan solution, and an excess of hydrochloric acid solution (6 mol / L) was slowly added to the mixed suspension, and the mixture was kept still until a chitosan hydrogel was formed, which was recorded as Ch hydrogel.

[0060] like Figure 3 As shown in Figure 2, the peaks of AM / Ch hydrogel at 2θ = 6.1°, 38.20°, 44.40°, 64.60°, 77.60°, and 81.76° can be compared with those of Ti3C2T x The peak intensity of chitosan decreased significantly after cross-linking, which confirmed the decrease of crystallinity after cross-linking.

[0061] Example 5

[0062] Escherichia coli (CMCC 44102) and Staphylococcus aureus (CMCC 26003) were used as typical bacterial models for antibacterial experiments. The plate count method was used to evaluate the antibacterial performance of the samples. Escherichia coli and Staphylococcus aureus were incubated in LB medium and brain heart infusion (BHI) medium at 37°C for 24 hours. The active bacterial solution (1.0×10 8 To verify the photothermal antibacterial properties of the hydrogel, 2.5 g of the hydrogel sample was added to 4 mL of bacterial solution and then exposed to simulated sunlight (0.2 W / cm 2) for 60 min. Take an appropriate amount of diluted bacterial solution and spread it on an agar plate, incubate at 37°C for 24 h, and quantitatively count the number of colonies. Figure 4 As shown in the figure, AM / Ch hydrogel has excellent light-induced antibacterial properties against Staphylococcus aureus and Escherichia coli, killing 58.34% of Escherichia coli and 35.09% of Staphylococcus aureus after 15 minutes of illumination. The antibacterial property of AM / Ch hydrogel is better than that of Ch hydrogel.

[0063] Example 6

[0064] 2g LiF was slowly added to a polytetrafluoroethylene beaker containing 30ml hydrochloric acid (12mol / L) and stirred at 35°C for 30 minutes to obtain an etching solution. 2g Ti3AlC2 powder was slowly added to the above solution and kept at 35°C for 24 hours. After the etching process, the obtained product was repeatedly washed with deionized water and centrifuged at 3500rpm several times until the pH value was greater than 6. The obtained Ti3C2T x The clay was redispersed in deionized water, sonicated for 30 min, and hand-shaken to obtain a highly concentrated MXene suspension.

[0065] An appropriate amount of AgNO3 solution was added to the above MXene suspension under vigorous stirring to make the mass ratio of Ag:MXene = 2:8. Subsequently, an excess of sodium borohydride aqueous solution (1 mol / L) was quickly injected into the suspension under stirring, and the resulting suspension was further stirred for 30 minutes to produce an Ag / MXene composite material, which was centrifugally washed several times with deionized water and then freeze-dried.

[0066] 0.1 g of chitosan powder was added to 2.5 mL of acetic acid solution (0.42 mol / L) under stirring to produce a chitosan solution, and then 30 mg of Ag was added under stirring. 0.2 MXene 0.8 The powder is introduced into the chitosan solution. A cylindrical mold with a depth of 0.4 cm and a diameter of 1.9 cm is placed on top of an expandable polyethylene (EPE) foam with two circular holes with a diameter of 0.50 cm and a thickness of 0.1 cm. The bottom of the two holes of the EPE foam are sealed with tape. Then, the prepared chitosan suspension containing dispersed Ag / MXene powder is poured into the mold. After the suspension fills the two holes, hydrochloric acid solution (6 mol / L) is slowly added to finally complete the cross-linking process. After removing the mold and sealing, the AM / Ch hydrogel solar water evaporator is obtained. The preparation process is as follows Figure 5 As shown in a.

[0067] The AM1.5G solar simulator was used to simulate solar radiation, and the auxiliary detector was used to determine the solar radiation power density to be 0.2W / cm 2Place the evaporator in a beaker of water and weigh it every five minutes. Figure 5 b and c show that the evaporation rate of the AM / Ch hydrogel evaporator reaches 3.22 kg m -2 h -1 , is a pure water evaporator (0.83kg m -2 h -1 ) is 3.88 times.

[0068] The steam produced after evaporation is condensed and liquid water is collected. Inductively coupled plasma optical emission spectroscopy (ICP-OES) is used to compare the composition changes before and after desalination, and photoluminescence spectroscopy is used to compare the sewage purification effect. Figure 6 It can be concluded that the AM / Ch hydrogel evaporator has excellent seawater desalination and sewage purification performance. After seawater desalination, the ion concentration is significantly reduced by 3 to 4 orders of magnitude, and the methyl orange and methyl blue pollutants are completely removed.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite photothermal material, characterized in that: The following steps are involved: The MAX phase Ti3AlC2 powder was etched to remove Al and then washed repeatedly with deionized water to obtain Ti3C2T x , Ti3C2T x Re-dispersed in water, centrifuged after sonication, and obtained a high-concentration MXene suspension; The MXene suspension is added with an oxidizing silver ion solution under vigorous stirring, and after uniform mixing, an excess reducing agent is added and further stirred to obtain an Ag / MXene composite material, which is washed with deionized water and then freeze-dried; The mass ratio of silver to MXene in the oxidizing silver ion solution is 1-2:9-8; The Ag / MXene composite material is added to the chitosan solution under stirring, and then an excess of a cross-linking agent is added to the suspension, and the suspension is allowed to stand until an Ag / MXene / chitosan composite photothermal material is formed; The chitosan solution is an acetic acid solution of chitosan, and the concentration of the acetic acid is 0.4-0.5 mol / L; the cross-linking agent is a hydrochloric acid solution, and the concentration of the hydrochloric acid solution is 5-7 mol / L; The mass ratio of Ag / MXene composite material to chitosan is 0.25-0.35:

1.

2. The method for preparing the composite photothermal material according to claim 1, characterized in that: The etching method specifically comprises slowly adding LiF into hydrochloric acid to form an etching solution, then slowly adding Ti3AlC2 powder into the above solution and stirring, and keeping the temperature at 35°C for 24-48 hours; The mixture was washed repeatedly with deionized water until the pH was > 6; the ultrasonic time was 20-60 min.

3. The method for preparing the composite photothermal material according to claim 1, characterized in that: The oxidizing silver ion solution is a silver nitrate solution, the reducing agent is a sodium borohydride aqueous solution or a potassium borohydride aqueous solution, and the stirring time is 20-60 min.

4. A composite photothermal material, characterized in that: The composite photothermal material is obtained by the preparation method of the composite photothermal material according to claims 1-3.

5. The composite photothermal material according to claim 4, characterized in that: The Ag is Ag nanoparticles, the size of Ag is 2-15 nm, the MXene is a two-dimensional nanosheet, the Ag nanoparticles are uniformly dispersed on the MXene, and the chitosan is a three-dimensional structure.

6. Application of the composite photothermal material according to any one of claims 4 or 5 in the antibacterial field.

7. Application of the composite photothermal material according to any one of claims 4 or 5 in the field of water evaporation purification.